971 A Rare Case of a Reno-colic Fistula Presenting as a Retroperitoneal and Psoas Abscess. (12th October 2021) - Emmanuel, A; Gravestock, P; Thomas, D
Abstract: Background: Fistulous connections arising between the kidney and colon are rare and develop due to multiple aetiologies. We present a rare case of a reno-colic fistula presenting unusually as a retroperitoneal and psoas abscess managed surgically with a good outcome. Case Report: A 49-year-old lady presented with 5-day history of left flank pain and swelling with no significant surgical or medical history. Physical examination revealed a tender left renal angle with raised inflammatory markers (CRP and WCC). Computed tomography (CT) revealed an extensive collection extending from an atrophic left kidney through the retroperitoneum and psoas into the subcutaneous tissues with possible fistulation into the descending colon. This was initially treated with antibiotics and percutaneous drainage of the collection. A reno-colic fistula was confirmed via left retrograde pyelogram. Under the multidisciplinary care of the urology and colorectal general surgical teams she underwent a left nephrectomy, large bowel resection and defunctioning colostomy successfully and was discharged eight days later. Histology later confirmed an extensively scarred atrophic left kidney with multiple renal stones with no preserved glomeruli, focal inflammatory infiltrate and stromal calcification consistent with end stage nephropathy. With the resected 5 cm descending colon showing mucosal and serosal inflammation consistent with site of fistula. Conclusions: Reno-colic fistula is rare and presentation with a retroperitoneal and psoas abscess uncommon. We report a rare case of a reno-colic fistula secondary to a chronically infected and obstructed left kidney managed surgically with a good outcome.